Early stages of development in Mediterranean red coral (Corallium rubrum): The key role of sclerites - Bruna Giordano; Bruna Giordano; Bruna Giordano; Lorenzo Bramanti; Jonathan Perrin; Ozan Kahramanoğulları; Daniel Vielzeuf (Frontiers in Marine Science, 2023)
Corals are ecosystem engineers whose tree-like structures give three-dimensional complexity to the habitat. Their population dynamics are affected by recruitment and juvenile survival. Therefore, several defense strategies, such as the formation of hard skeletons and/or spicules, have evolved to protect these vulnerable stages. The family Coralliidae, to which “precious corals” belong, represent an exception in the order Scleralcyonacea, as they form hard CaCO3 skeletons and small CaCO3 structures, the sclerites. The skeletogenesis of Corallium species is relatively well documented in adult colonies but remains poorly known in the early stages of the development of new colonies. To shed light on the timing of Corallium rubrum’s early skeleton formation and the role of sclerites, we focused on the first 4-years of life, applying different techniques, from scanning electron microscopy to synchrotron tomography and laser ablation inductively coupled plasma-mass spectrometry. Our results show that: 1) the first visible sclerites in the primary polyp appear at least 12 days after larval settlement, which is associated with a high CaCO3 production rate (4.5 ± 2.3 μg of CaCO3 per day). Furthermore, growth rings are visible in the sclerites, showing that fully matured sclerites grow fast, probably in 3 to 4 days. 2) Sclerites are the only biomineral product in the first year of life of C. rubrum’s colonies. 3) The evidence of a consolidated axial skeleton, intended as the inner part of the skeleton characteristic of the adult red coral (the medullary zone, MZ), is recorded for the first time in 2-year-old colonies. 4) The annular zone (AZ) around the medullary zone starts forming not before four years after settlement. Thus, primary polyp builds a deformable armor made of only sclerites during the first year. This shelter provides mechanical protection from abrasion and predation to early settled colonies. After two years, settlers are firmly and mineralogically attached to the substratum, which makes them less vulnerable to predation than younger recruits that are not anchored by the skeleton.